“One Mother” painting on wood, Keels, NL - Whitney, Erin (2012)
Painting on wood on wall of main room in the home of Gordon Hobbs, most recently inhabited by Reg Hobbs (deceased). Depicts a woman sitting and knitting with a cat playing with her ball of yarn. Text reads “ONE MOTHER/If friend or Sweetheart/we should lose, we can/get another. But in this life/to each of us is given just/one Mother.”